Comparative assessment of the human and animal health surveillance systems in Tanzania: Opportunities for an integrated one health surveillance platform - Irene R. Mremi; Susan F. Rumisha; Calvin Sindato; Sharadhuli I. Kimera; Leonard E.G. Mboera (Taylor & Francis Group, 2023)
ABSTRACTGlobally, there have been calls for an integrated zoonotic disease surveillance system. This study aimed to assess human and animal health surveillance systems to identify opportunities for One Health surveillance platform in Tanzania. A desk review of policies, acts and strategies addressing disease surveillance that support inter-sectoral collaboration was conducted. A semi-structured questionnaire was administered to key informants from the two sectors. Databases with potential relevance for surveillance were assessed. One Health-focused policies, acts, strategic plans and guidelines emphasising inter-sectoral collaboration strengthening were in place. Stable systems for collecting surveillance data with trained staff to implement surveillance activities at all levels in both sectors were available. While the human surveillance system was a mix of paper-based and web-based, the animal health system was mainly paper-based. The laboratory information system existed in both sectors, though not integrated with the epidemiological surveillance systems. Both the animal and human surveillance systems had low sensitivity to alert outbreaks. The findings indicate that individual, organisational, and infrastructure opportunities that support the integration of surveillance systems from multiple sectors exist. Challenges related to data sharing and quality need to be addressed for the effective implementation of the platform.